ANALISIS PENGARUH PENGELUARAN PERKAPITA KEBUTUHAN DASAR DAN PENDIDIKAN TERHADAP KEMISKINAN DI PROVINSI SUMATERA UTARA - Nasution, Ainil Hafizha; Rakhmawati, Fibri; Aprilia, Rima (UIN Imam Bonjol Padang, 2023)
Many factors can cause poverty such as low income, health, education and the powerlessness or inability of certain people to be able to participate in development in their country. Education is one of the most influential aspects, especially for the development of human resources. Poverty can also be measured by the ability of the community to meet their basic needs or needs in the form of food and non-food. This study aims to determine how big the impact or influence of each independent variable on the dependent variable using panel data regression method consisting of cross section and time series. The panel data regression method with a fixed effect approach to the individual effects model has a result of R2 of 99,63% where the per capita expenditure variables for basic needs and school dropout rates are factors that have a significant effect on poverty in North Sumatra Province and the p-value results from the partial test (t-test) expeniture per capita for basic needs is 4,841 1,984 and the dropout rate is 3,733 1,984.